The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jvim.16375
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in dogs: Etiology, clinical and clinicopathologic findings, prognostic markers, and outcome

Abstract: Background Acute kidney injury (AKI) is a common, potentially fatal condition. Objectives To characterize the etiologies, clinical and clinicopathologic findings, hospitalization period, and outcome of dogs with AKI and to identify markers of negative prognosis. Animals Two hundred forty‐nine client‐own dogs diagnosed with AKI and hospitalized at a veterinary teaching hospital. Methods Retrospective study. Search of medical records for dogs with AKI. Results Common clinical signs included lethargy (225/249, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
5
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 34 publications
2
29
5
5
Order By: Relevance
“…Most recently, a retrospective study of 249 dogs found a lower overall mortality rate of 34%, with higher rates of mortality associated with higher grades of AKI (Rimer et al . 2022). Similarly, dogs who died in our study tended to have a higher creatinine than those who survived, although the sample size was too small for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a retrospective study of 249 dogs found a lower overall mortality rate of 34%, with higher rates of mortality associated with higher grades of AKI (Rimer et al . 2022). Similarly, dogs who died in our study tended to have a higher creatinine than those who survived, although the sample size was too small for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…AKI has previously been associated with high mortality rates and a recent metaanalysis found an overall mortality of 53.1% in cats and 45% in dogs, although infectious aetiologies were associated with a lower mortality rate (Legatti et al 2018). Most recently, a retrospective study of 249 dogs found a lower overall mortality rate of 34%, with higher rates of mortality associated with higher grades of AKI (Rimer et al 2022). Similarly, dogs who died in our study tended to have a higher creatinine than those who survived, although the sample size was too small for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Short-term prognosis of AKI is affected by multiple factors including the etiology (which influences the reversibility of the injury), comorbidities, complications, and treatment options. 3,4 In 2 large scale studies of AKI in dogs managed medically or by hemodialysis, short-term mortality rates were 56% (56/99 dogs) and 47% (86/182 dogs), respectively. 2,3 In the former study, 19/43 dogs (44%) that were discharged from the hospital had serum creatinine concentration (sCr) within the reference range during the follow-up period, whereas in the remaining 56% sCr remained above the reference range, and subsequently these dogs were diagnosed with chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) results from multiple aetiologies and is associated with mortality as high as 50%–60% in dogs and cats 1–3 . The prevalence of hospital‐acquired AKI is increasing, and AKI is a risk factor for in‐hospital mortality 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) results from multiple aetiologies and is associated with mortality as high as 50%-60% in dogs and cats. [1][2][3] The prevalence of hospital-acquired AKI is increasing, and AKI is a risk factor for in-hospital mortality. 4 The diagnosis of AKI early in its course may improve survival by facilitating prompt, appropriate therapeutic intervention before renal parenchymal lesions become irreversible and severe uraemia ensues.…”
Section: Introductionmentioning
confidence: 99%